Tryptophan-2,3-dioxygenase is regulated by prostaglandin E2 in malignant glioma via a positive signaling loop involving prostaglandin E receptor-4 - Sahm, Katharina; Ott, Martina; Rauschenbach, Katharina; Deumelandt, Katrin; Sahm, Felix; Opitz, Christiane; Deimling, Andreas von; Wick, Wolfgang; Platten, Michael (Journal of neurochemistry, 2016)
Malignant gliomas and other types of tumors generate a local immunosuppressive microenvironment, which prohibits an effective anti-tumor immune response and promotes tumor growth. Along with others, we have recently demonstrated that catabolism of the essential amino acid tryptophan via tryptophan-2,3-dioxygenase (TDO) is an important mechanism mediating tumor-associated immunosuppression particularly in gliomas. The pathways regulating TDO in tumors, however, are poorly understood. Here, we show that prostaglandins enhance TDO expression and enzymatic activity in malignant gliomas via activation of prostaglandin E receptor-4 (EP4). Stimulation with prostaglandin E2 (PGE2) up-regulated TDO-mediated kynurenine release in human glioma cell lines, whereas knockdown of the PGE2 receptor EP4 inhibited TDO expression and activity. In human malignant glioma tissue expression of the PGE2-producing enzyme cyclooxygenase-2 (COX2) and its receptor EP4 were associated with TDO expression both on transcript and protein level. High expression of EP4 correlated with poor survival in malignant glioma patients WHO III-IV. Importantly, treatment of glioma cells with an EP4 inhibitor decreased TDO expression and activity. Moreover, TDO-over-expressing murine gliomas showed increased COX2 and EP4 expression suggesting a positive feedback mechanism in vivo. In summary, targeting EP4 may inhibit - in addition to immunosuppressive COX2 signaling - tryptophan degradation as another important immunosuppressive pathway and thus, could provide a dual clinically relevant immunotherapeutic avenue for the treatment of malignant gliomas. We proposed that in malignant gliomas prostaglandin E2 (PGE2) produced by cyclooxygenases (COX) up-regulates tryptophan-2,3-dioxygenase (TDO) expression and enzyme activity through binding to its Gs-coupled receptor EP4 and therefore may mediate tumor immune escape in part through aryl hydrocarbon receptor (AHR) activation. Moreover, TDO activity itself seems to induce intratumoral PGE2 metabolism suggesting an immunosuppressive loop involving COX/EP4/TDO.
First published: 27 December 2015
Gesehen am 04.03.2020